Light-Controllable PROTACs for Temporospatial Control of Protein Degradation - Liu, Jing; Peng, Yunhua; Wei, Wenyi (Frontiers in Cell and Developmental Biology, 2021)
PROteolysis-TArgeting Chimeras (PROTACs) is an emerging and promising approach to target intracellular proteins for ubiquitination-mediated degradation, including those so-called undruggable protein targets, such as transcriptional factors and scaffold proteins. To date, plenty of PROTACs have been developed to degrade various disease-relevant proteins, such as ER, AR, RTK and CDKs. However, the on-target off-tissue and off-target effect is one of the major limitations that prevent the usage of PROTACs in clinic. To this end, we and several other groups have recently developed light-controllable PROTACs, as the representative for the third generation controllable PROTACs, by using either photo-caging or photo-switch approaches. In this review, we summarize the emerging light-controllable PROTACs and the prospective for other potential ways to achieve temporospatial control of PROTACs.